2016
DOI: 10.1159/000446873
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Dying Vocal Fold Epithelial Cells by Ultrastructural Features and TUNEL Method

Abstract: Cell death is a regulated mechanism of eliminating cells to maintain tissue homeostasis. This study described 2 methodological procedures for evaluating cell death in the epithelium of immobilized, approximated and vibrated vocal folds from 12 New Zealand white breeder rabbits. The gold standard technique of transmission electron microscopy evaluated high-quality ultrastructural criteria of cell death and a common immunohistochemical marker, the terminal deoxynucleotidyl transferase dUTP nick end labeling meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 29 publications
1
6
0
Order By: Relevance
“…Rather, vocal folds that underwent approximation demonstrated the smallest epithelial cell nuclei area. These findings are in agreement with previous studies reporting the expression of TUNEL-labeled cells, condensed chromatin, and apoptotic bodies in the vocal folds after vibration and approximation (11). The present study adds to the body of literature objective quantification of TUNEL staining and the measurement of epithelial cell nuclei area.…”
Section: Discussionsupporting
confidence: 94%
See 3 more Smart Citations
“…Rather, vocal folds that underwent approximation demonstrated the smallest epithelial cell nuclei area. These findings are in agreement with previous studies reporting the expression of TUNEL-labeled cells, condensed chromatin, and apoptotic bodies in the vocal folds after vibration and approximation (11). The present study adds to the body of literature objective quantification of TUNEL staining and the measurement of epithelial cell nuclei area.…”
Section: Discussionsupporting
confidence: 94%
“…Apoptosis, the most commonly studied type of programmed cell death, is the physiological elimination of cells (810). Several studies have reported that apoptosis occurs in the vocal folds in response to biomechanical trauma (1114). Following in vivo vocal fold vibration and vocal fold movement alone using a rabbit model, our laboratory observed morphological features of condensed chromatin and apoptotic bodies in vocal fold epithelial cells (11).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The most common of such epithelium-associated apoptotic processes are described in the context of laryngeal squamous cell carcinoma, leucoplakia, keratosis, epithelial hyperplasia, human papilloma virus (HPV) papilloma and few other benign lesions. Hence, this leads us to speculate that apoptotic cell death may at least partly contribute to the pathogenesis of diseases affecting the vocal fold epithelium [ 10 ]. Additionally, apoptosis has been described in the laryngeal epithelium in response to the physical stressors of abduction, adduction, and biochemical vibrations.…”
Section: Introductionmentioning
confidence: 99%